Implementasi Augmented Reality Sebagai Media Promosi Kursus Pembelajaran Pada LPPK Gentala Hospitality School Jambi - Fany, Rizky Gusti; M.Rakesh; Maria Rosario B (LPPM STIKOM Dinamika Bangsa, 2024)
The role of technology in this era is of significant importance in daily life. One of the technological innovations currently gaining attention is Augmented Reality. The utilization of Augmented Reality is considered an interesting method to introduce products sold by Transliving Jambi. The main challenge faced is the lack of understanding of the products, which has the potential to hinder the company's sales process. Therefore, the application currently being developed by the author is designed to utilize 3D object visualization. The use of tools such as Unreal Engine, Photoshop, and Blender forms the foundation for designing this application. The goal is to provide assistance to customers in better understanding information about the course learning media at LPPK Gentala Hospitality School Jambi. Thus, it is expected that this application will offer a deeper and more interactive experience for prospective customers.